370Measuring pneumococcal conjugate vaccine impact in a low-resource setting with minimal baseline data. (2nd September 2021) - Mollendorf, Claire von; Lim, Ruth; Choummanivong, Molina; Sychareun, Vanphanom; Vilivong, Keoudomphone; Lai, Jana Y.R.; Chan, Jocelyn; Dunne, Eileen M.; Phommachanh, Sysavanh; Moore, Kerryn; Ortika, Belinda D.; Gray, Amy; et al.
Abstract: Background: We aimed to measure 13-valent pneumococcal conjugate vaccine (PCV13) impact on various pneumococcal endpoints with minimal baseline data. Methods: PCV13 was introduced in October 2013 in Lao People's Democratic Republic. We implemented studies to evaluate PCV13 impact: retrospective record review of pneumonia cases for three years pre-PCV13; prospective study of acute respiratory infection (ARI) for 4.5 years post-PCV to demonstrate effectiveness against hypoxic pneumonia; invasive pneumococcal disease (IPD) surveillance (2004-2019); carriage in children hospitalised with ARI (2013-2019); and community carriage surveys pre- and two years post-PCV13. Results: Annual incidence of hospitalized pneumonia pre-PCV13 in children 2-59 months was 1, 530 (95% confidence interval [CI] 1, 477-1, 584) per 100, 000. Vaccine effectiveness against hypoxic pneumonia was 37% (95% CI 6-57%). In children <5 years, 85% (11/13) of IPD cases were due to PCV13 serotypes pre-PCV13, and 43% (3/7) post-PCV13; and in individuals ≥5 years, 61% (27/44) and 42% (17/40), respectively. In hospitalised children, vaccine type carriage prevalence reduced from 20.0% (95% CI 15.2-24.9%) in 2013 to 12.8% (95% CI 8.5-17.1%) in 2019 with increasing vaccine coverage. Results were consistent with community carriage studies. Conclusions: Despite limited baseline data in Laos, we found evidence of PCV13 impact using a variety of methods. Our approach could be used in similar settings to augment existing WHO guidelines. Key messages: A combination of methods may be useful to determine the impact of vaccine introduction in countries with limited surveillance.